Consciousness & Creation A Study of the Process of Communication and Innovation in the Design of Contemporary Urban Monuments - Malik, Rashaa; Hadi, Alaa (ICONARCH International Congress of Architecture and Planning, 2014)
The main message that any architectural work carries is related to the objective facts and literal meanings. Architecture "in the eyes of the theorists" has always been in between. Architecture has the physical characteristics that enable it to be declared as visual engineering facts. On the other hand the vision of creative architectural works around us cannot be emptied from the poetic literal performance as a literal work. Connection happens when the recipient has reaction towards the architectural work. At this point the ultimate aim for this processes happens in two directions. To communicate with the Architectural work, there should be a process of the characteristics of the human mind to respond to the perception so that the recipient understands the architectural work . Depending on the process of perception which depends on the human mind and its awareness taste of Architecture through analysis. The relation between man and architecture is the main point of poetic relation of architecture because it is, space and place, therefore, two main directions can be found between the recipient and the architect which is the connection. The objective is to find a mechanism that help to measure the degree of similarity between the creator interpretation and the recipient of the creative architectural work through the signal concept which depends on the literal studies and the poetic concept in architecture which is used to measure the general taste of humans. Hypothesis of the study can be illustrated as" architecture creative process cannot reach its perfectness unless the schemata of the recipient reach its ultimate while his evaluation of the architectural-product". It’s the positive understanding of the architectural work through the communicative relation with the viewer.